Learning Environment: Gender Profile of Students' Pro-Environmental Behavior (PEB) based on Green Consumerism - Ichsan, Ilmi Zajuli; Sigit, Diana Vivanti; Miarsyah, Mieke (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
The damage to nature and the changing situation of the surrounding environment certainly make you anxious. The role of students in safeguarding nature is certainly one of the important points in determining the sustainability of green consumerism. The purpose of this study is to see the influence of gender in the students' Pro-Environmental Behavior (PEB) in understanding the concept of green consumerism. The research was conducted in July-August 2018. The research was located at State Junior High School (SMPN) 1 of South Tambun, Bekasi, West Java, Indonesia. The method used was a survey with simple random sampling to obtain 214 samples consisted of 107 male students and 107 female students. PEB score of male students was 63.86 and 64.34 for female students. Data analysis used was t-test with a confidence level of 95%. The results of the t-test showed that there were no differences in green consumerism in terms Pro-Environmental Behavior between male and female. This shows that there needs to be an effort in evaluation by the teachers to improve the male and female students Pro-Environmental Behavior.